Association of gut microbiota and short-chain fatty acids with pre-diabetes and diabetes following gestational diabetes - Gao, Beibei; Shen, Qiong; Yang, Jingyu; Wu, Ying; Hu, Dandan; Chen, Lei (Frontiers in Microbiology, 2026)
BackgroundEmerging evidence demonstrates correlations among the gut microbiota, fecal short-chain fatty acids (SCFAs) and glucose metabolism. Few studies focus on post-gestational diabetes women. This study aimed to compare the gut microbiota and fecal SCFAs among different states of postpartum glucose metabolism in women with previous gestational diabetes mellitus (p-GDM).MethodsThe study finally recruited 60 women with p-GDM including 16 healthy controls (HC), 40 Pre-diabetes (Pre-DM) patients and 4 type 2 diabetes patients according to a 2-h 75-g oral glucose tolerance. Stool samples were obtained 1–5 years after delivery. Gut microbiota was obtained by sequencing V3–V4 region of 16S rRNA gene and fecal SCFAs were measured by gas chromatography-mass spectrometry. The microbial community structure of the Pre-DM group, as revealed by principal coordinates analysis (PCoA), exhibited distinct clustering that was further validated by hierarchical clustering, definitively identifying two subgroups: Pre-DM1 and Pre-DM2. The primary analyses in this report compared the HC and Pre-DM groups, with a particular focus on a three-group comparison (HC vs. Pre-DM1 vs. Pre-DM2) to demonstrate heterogeneity within Pre-DM. For the type 2 diabetes group, only descriptive statistics were presented, without formal statistical testing.ResultsNo significant differences were observed in age, BMI and months post-delivery between HC and Pre-DM group. The Pre-DM group exhibited two distinct clustering patterns: Pre-DM1 (n = 25) and Pre-DM2 (n = 15). The gut microbiota structure of Pre-DM1 largely overlapped with the HC group, while Pre-DM2 was closer to the type 2 diabetes group. Compared to the HC group, the relative abundance of Faecalibacterium, Ruminococcus, and Subdoligranulum remained unchanged in Pre-DM1 group, while significantly reduced in Pre-DM2 group. Furthermore, compared with HC group, acetic acid and propionic acid were increased in the Pre-DM1 group while were similar to Pre-DM2. HC group had higher concentration of caproic acid than Pre-DM1 (P = 0.01) and Pre-DM2 (P = 0.02).ConclusionsOur study discovered that dysbiosis of the gut microbial structure and alterations in SCFAs had already been present in women with Pre-DM and further revealed two subsets of Pre-DM with remarkable heterogeneity. Further studies are needed to explore whether the heterogeneity can help predict postpartum glycemic states.